Scissurella nesbittae, new species, from the Gries Ranch Formation, Lewis County, Washington State (Gastropoda: Vetigastropoda: Scissurellidae) - Geiger, Daniel L.; Goedert, James L. (Zootaxa, 2020)
Recent and fossil global scissurellids were monographed by Geiger (2012) and additional species were recently described from Brazil (Pimenta & Geiger 2015). Here, we describe an additional fossil species from shallow water strata of the late Eocene Gries Ranch Formation in Lewis County, Washington State, USA.